1988
DOI: 10.1021/bi00412a008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro protein kinase C phosphorylation sites of placental lipocortin

Abstract: Human placental lipocortin is a high-affinity substrate for rat brain protein kinase C in vitro with phosphorylation occurring on serine and threonine residues in a ratio of approximately 2 to 1. Comparison of the ability of various N-terminal-truncated derivatives of lipocortin to serve as phosphorylation substrates, and direct analysis of the N-terminal peptides cleaved from 32P-labeled lipocortin, indicated that threonine-24, serine-27, and serine-28 were the phosphorylation sites. The possibility is discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…Human lipocortin 1 has been shown to be a substrate for epidermal growth factor receptor kinase (Pepinski & Sinclair, 1986;Haigler et al, 1987;Futter et al, 1993) and protein kinase C (Varticovski et al, 1988;Schlaepfer & Haigler, 1988;Oudinet et al, 1993). Lipocortin 1 has also been implicated in the regulation of signal transduction pathways involving phospholipase A2 inhibition (Kim et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Human lipocortin 1 has been shown to be a substrate for epidermal growth factor receptor kinase (Pepinski & Sinclair, 1986;Haigler et al, 1987;Futter et al, 1993) and protein kinase C (Varticovski et al, 1988;Schlaepfer & Haigler, 1988;Oudinet et al, 1993). Lipocortin 1 has also been implicated in the regulation of signal transduction pathways involving phospholipase A2 inhibition (Kim et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PKC by growth factors, hormones or phorbol esters leads to the phosphorylation of many endogenous proteins which mediate the effects of these agonists on cellular processes such as proliferation and differentiation. Annexins are among these substrates phosphorylated by PKC (Khanna et al, 1986;Schlaepfer and Haigler, 1988;Antonicelli et al, 1989;Isacke et al, 1986;Could et al, 2986). In mesangial cells, we have shown that actiCrmespondence to J.-P. Oudinet PtdIns(4,5)P2, phosphatidylinositol 4,s-bisphosphate; Ins(l,4,5)P3, inositol 1,4,5-trisphosphate; acyl,Gro, diacylglycerol; PKC, protein kinase C; c-, conventional; n-, novel; a-, atypical.…”
mentioning
confidence: 99%
“…The pi of the phosphorylated form of lipocortin I was different (66) from that of the non-phosphorylated molecules (6,9), This may indicate either that all molecules were not phosphorylated under our experimental conditions (3 min) or that the lipocortin I molecule population is heterogeneous. The latter could explain the lack of phosphorylation of particulate lipocortins.…”
Section: Discussionmentioning
confidence: 79%